Explaining Green Purchase Intention among Generation Z: A Structural Equation Modeling Approach Based on the Theory of Planned Behaviour - Khoiriani, Annida; Triwinarso, Arif (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the determinants of green purchase intention among Generation Z consumers in Indonesia by analyzing the roles of green advertising and green product innovation, with green brand image acting as a mediating variable. Although research on sustainable consumption has grown significantly, limited studies have explained how marketing communication and product innovation jointly influence green purchase intention through brand perception, particularly among Generation Z in emerging markets. Grounded in the Theory of Planned Behavior (TPB), this study proposes a structural model explaining how marketing-related stimuli influence consumer behavioral intention through cognitive brand evaluation. A quantitative survey was conducted with 250 Generation Z respondents in Indonesia, and the data were analyzed using Structural Equation Modeling (SEM) with AMOS 24. The results reveal that green advertising and green product innovation significantly influence green brand image, which in turn has a strong positive effect on green purchase intention. The findings confirm that green brand image plays a mediating role in translating sustainability-oriented marketing strategies into consumer behavioral intentions. Theoretically, this study extends the TPB framework by highlighting the role of brand perception as a cognitive mechanism linking marketing stimuli and behavioral intention in the context of sustainable consumption. Practically, the results suggest that firms should strengthen sustainability communication and continuously innovate environmentally friendly products to build a credible green brand image among young consumers. Nevertheless, the study is limited by its cross-sectional design and the dominance of highly educated respondents, which may restrict the generalizability of the findings.